PENGARUH LAMA PEREBUSAN SIMPLISIA DAUN APAH (Albertisia papuana Becc.) YANG DIGUNAKAN SEBAGAI PENYEDAP MAKANAN OLEH MASYARAKAT KAB. TANA TIDUNG TERHADAP ANGKA CEMARAN MIKROBA - Rosnah Rosnah; Medi Hendra; Eko Kusumawati (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
The purpose of this study is to determine the effect of long simplicia Apah’s leaves (Albertisia papuana Becc.) that’s used as a food’s flavoring by people of Kab. Tana Tidung against microbial contamination numbers. The design of research used a pattern completely randomized design (RAL), with a dilution series of samples 10-8, 10-9 and 10-10 and different boiling’s level (5, 10, 15, 20 and 25 minutes). The results obtained that the longer of boiling process is used, then the less the number of microbial contamination of colony growth. Average number of microbial contamination in samples in the boiling of 5 minutes is 92 x 1010 microbial colonies, in boiling 10 minutes is 87 x 1010 microbial colonies, in boiling 15 minutes is 56 x 1010 microbial colonies, in boiling 20 min is 44 x 1010 colonies of microbes and the boiling simplicia infuse for 25 minutes is 33 x 1010 colonies of microbes. Based of Analysis variance variety in each treatment showed that in boiling 20 minutes and 25 minutes showed real significant difference (p <0.05), but the boiling 5, 10 and 15 minutes there was no significant difference (P> 0.05). The results of the Anova, showed that in boiling treatment of simplicia Apah’s leaves (Albertisia papuana Becc.) significantly affects the growth of microbial colonies. Analysis of Least Significant Difference (LSD) at the level of 95%, the result that the effects of long boiling the simplicia Apah’s leaves (Albertisia papuana Becc.) which is used as a food flavoring by people of Kab. Tana Tidung, significant effect on the numbers of microbial contamination